Plug nose refractory for preventing clogging and its use

CN122940445APending Publication Date: 2026-10-20TANGSHAN IRON & STEEL GROUP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510976440.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种预防结瘤的塞棒棒头耐火材料及其应用,以解决上述塞棒棒头抗氧化性能较差,钢液与耐火材料之间润湿性较强导致棒头结瘤层累积的问题

Benefits of technology

[0025]本发明向耐火材料中引入CMA细粉和SiC,将其应用于塞棒棒头的制备过程中,利用SiC良好的抗氧化性能,能够提升塞棒棒头的抗氧化性能,从而减少塞棒棒头中碳的氧化,抑制脱碳层的形成,同时CMA与钢液润湿性差,能够降低钢液与塞棒棒头之间的润湿性,降低钢中夹杂物在塞棒棒头表面的富集,从而减少塞棒棒头的结瘤层厚度,提升连铸工艺的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005501578030000051
    Figure BDA0005501578030000051
  • Figure BDA0005501578030000061
    Figure BDA0005501578030000061
  • Figure BDA0005501578030000071
    Figure BDA0005501578030000071
Patent Text Reader

Abstract

This invention discloses a stopper rod head refractory material for preventing nodule formation and its application. The stopper rod head refractory material comprises powder and resin base. By weight percentage, the powder includes 56-66% tabular corundum, 5% magnesia, 8% activated alumina, 0-8% CMA fine powder, 15% graphite, 3% Si powder, 3% Al powder, and 0-8% SiC. The resin base is phenolic resin, which accounts for 5% of the powder weight. The refractory material is mixed, pressed, and heat-treated to produce the stopper rod head. The resulting stopper rod head combines excellent oxidation resistance and nodule prevention properties, solving the problem of nodule blockage in the stopper rod head during continuous casting in the tundish, and preventing casting instability caused by nodule formation in the stopper rod head during continuous casting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory materials technology, and in particular to a stopper rod head refractory material for preventing nodulation and its application. Background Technology

[0002] The continuous casting process of molten steel includes the following steps: (1) Molten steel preparation: Molten steel smelted in the steelmaking furnace is processed and then transferred to the ladle to prepare for casting; (2) Tundish operation: Molten steel enters the tundish from the ladle through the sliding nozzle. The tundish plays the role of buffering, separating and purifying the molten steel; (3) Solidification in the crystallizer: Molten steel is injected into the crystallizer through the submerged entry nozzle, at which point the initial billet shell begins to form; (4) Secondary cooling: As the billet moves downward through the cooling section, it is further cooled and solidified; (5) Finally, straightening, cutting, deburring and surface treatment are performed. In the continuous casting process, the stopper rod is installed inside the tundish and usually works in conjunction with the submerged entry nozzle in the crystallizer. The lifting and lowering action of the stopper rod realizes the precise control of the molten steel flow rate and plays the role of throttling regulation. Some stopper rods with an integral structure can continuously blow argon gas into the molten steel. In addition to throttling, such stopper rods can also effectively reduce the problem of nozzle nodule formation, reduce the impurity content of the billet, and thus improve the quality of the billet. As a core component in continuous casting, the stopper rod plays a decisive role in ensuring the continuity of the continuous casting process and the quality of the steel billet.

[0003] Currently, Al2O3-C stopper rods are key refractory materials widely used in continuous casting processes. Chinese patent CN113526965A discloses a stopper rod for continuous casting of high-oxygen steel. The rod head is made of Spinel-C material, with a chemical composition by weight percentage of Al2O3: 60-72%, MgO: 20-30%, C: 5-10%, and the remainder being trace impurities. It also contains added antioxidants and phenolic resin binders. The antioxidant is metallic aluminum. When these rod heads are used as stopper rods in high-oxygen steel casting, they do not form low-melting-point phases, exhibit good corrosion resistance, reduce carbon gain in molten steel, and increase the number of consecutive castings. However, in practical applications, the stopper rod head is prone to oxidation and decarburization due to prolonged contact with molten steel. Simultaneously, the strong wettability between molten steel and the refractory material makes it easy for inclusions in the steel to adhere to the surface of the stopper rod head. Especially when casting aluminum-deoxidized steel, easily oxidized elements such as Al in the molten steel will generate Al2O3, which is more likely to adhere to the surface of the stopper rod head, forming a nodule layer on the surface of the stopper rod head. As the casting time and number of castings increase, the nodule layer gradually thickens, eventually causing casting instability. In severe cases, the nodule will fall off into the molten steel, forming a large number of non-metallic inclusions, thereby reducing the cleanliness of the molten steel.

[0004] Therefore, how to improve the oxidation resistance of the stopper rod head by optimizing the material of the stopper rod head, while reducing the wettability of molten steel and refractory materials, and improving the castability of aluminum deoxidized steel, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a refractory material for the stopper rod head that prevents nodulation and its application, in order to solve the problems of poor oxidation resistance of the stopper rod head and strong wettability between molten steel and refractory material leading to the accumulation of nodulation layer on the rod head.

[0006] To achieve the above objectives, the first aspect of the present invention provides a stopper rod head refractory material for preventing nodulation. The stopper rod head refractory material comprises powder and resin base material. By weight percentage, the powder comprises 56-66% tabular corundum, 5% magnesia, 8% activated alumina, 0-8% CMA fine powder, 15% graphite, 3% Si powder, 3% Al powder, and 0-8% SiC. The resin base material is phenolic resin, which accounts for 5% of the weight of the powder.

[0007] Preferably, the particle size of the tabular corundum is 0-1 mm, wherein the Al2O3 content in the tabular corundum is ≥98%.

[0008] Preferably, the particle size of the tabular corundum is 0-0.5 mm, wherein the Al2O3 content in the tabular corundum is ≥98%.

[0009] Preferably, the particle size of the tabular corundum is 325 mesh, wherein the Al2O3 content in the tabular corundum is ≥98%.

[0010] Preferably, the particle size of the magnesia is 180 mesh, and the MgO content in the magnesia is 97% to 98%.

[0011] Preferably, the particle size of the activated alumina is 325 mesh, and the Al2O3 content in the activated alumina is ≥99wt%.

[0012] Preferably, the particle size of the CMA fine powder is 200 mesh, wherein, by weight percentage, the CMA fine powder contains 70% Al2O3, 10% MgO, and 20% CaO.

[0013] Preferably, the CMA fine powder contains three phases: MgAl2O4, CaAl2O4, and CaAl4O7. By weight percentage, MgAl2O4 accounts for 70%, CaAl2O4 accounts for 20%, and CaAl4O7 accounts for 10%.

[0014] Preferably, the graphite has a particle size of 100 mesh, wherein the C content is ≥99%; the Si powder has a particle size of 325 mesh, wherein the Si content is ≥99%; the Al powder has a particle size of 325 mesh, wherein the Al content is ≥99%; and the SiC has a particle size of 325 mesh, wherein the SiC content is ≥98.5%.

[0015] A second aspect of the present invention provides a method for preparing a stopper rod head for preventing nodule formation, which is prepared using the above-mentioned stopper rod head refractory material.

[0016] Preferably, a method for preparing the tip of a stopper rod for preventing nodule formation includes the following steps:

[0017] (1) Dry mix tabular corundum, activated alumina and magnesia, then add phenolic resin and continue mixing to obtain mixture one;

[0018] (2) Mix CMA fine powder, graphite, Si powder, Al powder and SiC to obtain mixture two;

[0019] (3) Add mixture 2 to mixture 1 and mix well to obtain mixture 2;

[0020] (4) Press the mixture into standard bar blanks using an isostatic press;

[0021] (5) Sinter the standard rod blank to obtain the stopper rod head.

[0022] Preferably, in step (1), the dry mixing time is 3 to 10 minutes, and the continued mixing time is 10 to 30 minutes.

[0023] Preferably, in step (5), the sintering temperature is 250-350℃ and the time is 20-30h.

[0024] Therefore, the present invention, employing the above-mentioned refractory material for preventing nodulation of stopper rods and its application, has the following beneficial effects:

[0025] This invention introduces CMA fine powder and SiC into refractory materials and applies them to the preparation process of stopper rod heads. Utilizing the excellent antioxidant properties of SiC, the antioxidant properties of the stopper rod head can be improved, thereby reducing carbon oxidation in the stopper rod head and inhibiting the formation of a decarburized layer. Simultaneously, the poor wettability of CMA with molten steel reduces the wettability between the molten steel and the stopper rod head, reducing the enrichment of inclusions in the steel on the surface of the stopper rod head, thus reducing the thickness of the nodule layer on the stopper rod head and improving the stability of the continuous casting process.

[0026] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the wetting angle of the refractory material in Comparative Example 1 during a high-temperature wetting experiment.

[0028] Figure 2 This is a schematic diagram of the wetting angle of the refractory material in Example 1 during the high-temperature wetting experiment;

[0029] Figure 3This is a schematic diagram of the wetting angle of the refractory material in Example 2 during the high-temperature wetting experiment.

[0030] Figure 4 This is a schematic diagram of the wetting angle of the refractory material in Example 3 during the high-temperature wetting experiment.

[0031] Figure 5 This is a schematic diagram of the wetting angle of the refractory material in Example 4 during the high-temperature wetting experiment.

[0032] Figure 6 The results of the antioxidant performance test of the stopper rod head in the example are shown. Detailed Implementation

[0033] The present invention will be further described below. It should be noted that this embodiment is based on the present technical solution and provides detailed implementation methods and specific operation processes, but the present invention is not limited to this embodiment.

[0034] The raw materials used in the examples are from the following sources:

[0035] The tabular corundum has a grain size of 0.5–1 mm and was purchased from Ammai Aluminum Co., Ltd.

[0036] The tabular corundum has a grain size of 0–0.5 mm and was purchased from Ammai Aluminum Co., Ltd.

[0037] The tabular corundum has a particle size of 325 mesh and was purchased from Ammai Aluminum Co., Ltd.

[0038] The fused magnesia has a particle size of 180 mesh and was purchased from Haicheng Zhonghao Magnesium Industry Co., Ltd.

[0039] The activated alumina had a particle size of 325 mesh and was purchased from Yunnan Yuntianhua Co., Ltd.

[0040] The CMA fine powder has a particle size of 200 mesh and was purchased from Engel Porcelain (Tianjin) New Material Technology Co., Ltd.

[0041] By weight percentage, the CMA fine powder contains 70% Al2O3, 10% MgO, and 20% CaO. The CMA fine powder also includes three phases: MgAl2O4, CaAl2O4, and CaAl4O7, with MgAl2O4 accounting for 70%, CaAl2O4 for 20%, and CaAl4O7 for 10% by weight. This CMA fine powder is a powder sintered at high temperature with a special morphology and specific phase composition, exhibiting good chemical stability, resistance to slag erosion, and non-wetting properties in molten steel, rather than being a powder composed solely of Al2O3, MgO, and CaO. Adding corresponding substances according to its composition would alter the properties of the stopper rod head, such as its flexural strength, compressive strength, and thermal shock resistance, and the anti-nodulation effect might not be consistent with the effect of this patent.

[0042] The graphite had a particle size of 100 mesh and was purchased from Dongguan Kaidi Carbon Co., Ltd.

[0043] The Si powder has a particle size of 325 mesh and was purchased from Hebei Wenlun Metal Materials Co., Ltd.

[0044] The Al powder has a particle size of 325 mesh and was purchased from Beijing Juguang Yingchuang Technology Co., Ltd.

[0045] The SiC particles were 325 mesh and were purchased from Ningxia Xingkai Silicon Industry Co., Ltd.

[0046] The phenolic resin, model PFSF-511, was purchased from Shandong Yonghui New Material Co., Ltd.

[0047] Comparative Example 1 and Examples 1-4 show the composition of the refractory material for the stopper rod head. The specific composition and the weight percentage of each raw material are shown in Table 1.

[0048] Table 1. Refractory material composition and proportion for comparative examples and embodiments.

[0049]

[0050]

[0051] Example 5

[0052] A method for preparing the tip of a plug for preventing nodule formation includes the following steps:

[0053] (1) Dry mix the tabular corundum, activated alumina and magnesia for 3 min, then add phenolic resin and continue mixing for 10 min to obtain mixture one;

[0054] (2) Mix CMA fine powder, graphite, Si powder, Al powder and SiC to obtain mixture two;

[0055] (3) Add mixture 2 to mixture 1 and mix well to obtain mixture 2;

[0056] (4) Press the mixture into standard bar blanks using an isostatic press;

[0057] (5) Dry the standard rod head blank at 300℃ for 12h to obtain the stopper rod head.

[0058] Test case

[0059] The refractory materials from Examples 1 to 4 were made into stopper rod heads according to the preparation method of Example 5, and the performance of the stopper rod heads was tested.

[0060] (1) The wetting angle between the prepared standard stopper rod head sample and the molten steel was measured using a high-temperature wetting angle instrument. The specific steps are as follows:

[0061] The high-temperature wetting angle measuring instrument was heated to 1550℃ at a heating rate of 20℃ / min and held at this temperature. After the furnace temperature stabilized, steel slag was placed on a thin sample sheet and placed into the resistance furnace via a moving arm. A high-definition camera and recorder were used to capture and record the wetting and spreading process of the steel sample on the sample surface. High-purity argon gas (greater than 99.9%) was used throughout the experiment to prevent sample oxidation. After the experiment, the sample was removed via the moving arm and cooled in air.

[0062] (2) According to the test method for oxidation resistance of carbon-containing refractory materials specified in the national standard GB / T 13244-1991, the end of the stopper rod after carbon burning was placed in a high-temperature furnace and heated to 1400℃ in an oxidizing atmosphere at a heating rate of 5℃ / min, and kept at that temperature for 2 hours. After it cooled to room temperature, it was cut radially and the thickness of the decarburized layer was measured.

[0063] The test results are shown in Table 2.

[0064] Table 2 Performance test results for comparative examples and embodiments

[0065]

[0066] Note: The change in wetting angle refers to the degree of change in the wetting angle of the embodiment compared to Comparative Example 1, and the change in oxidation index refers to the degree of change in the oxidation index of the embodiment compared to Comparative Example 1.

[0067] As can be seen from Table 2, after adding CMA fine powder and SiC to the refractory materials of Examples 1 to 4, compared with Comparative Example 1, the wetting angle increased, the wettability between steel and refractory material decreased, and the oxidation index decreased, indicating that the refractory materials prepared by the present invention have good oxidation resistance.

[0068] Depend on Figure 6It can be seen that the oxidation index of the stopper rod tip in the examples is lower than that in the control example (Comparative Example 1), indicating that the antioxidant properties of the examples are superior to those of Comparative Example 1. In Example 2, the stopper rod tip has the worst wettability with the molten steel and good antioxidant properties. Therefore, Example 2 is predicted to have better anti-nodulation properties.

[0069] The stopper rod head made in Comparative Example 1, along with those made in Examples 1 and 2, was used to cast bearing steel in the tundish of a steel plant for 8 heats. The stopper rods were then removed and cut in half, and the thickness of the nodules on the three types of stopper rod heads was compared. The comparison results are shown in Table 3.

[0070] Table 3. Nodule layer test results of the examples and comparative examples.

[0071]

[0072] The reduction rate of the plug tip nodule layer = (thickness of the plug tip nodule layer in Comparative Example 1 - thickness of the plug tip nodule layer in the Example) / thickness of the plug tip nodule layer in Comparative Example 1 × 100%.

[0073] As can be seen from Table 3, Example 2 contains a more suitable raw material ratio, which has a significant effect on preventing plug tip nodule formation and blockage, and the thickness of plug tip nodule formation is reduced by 52.38%.

[0074] The refractory material for preventing stopper rod tip nodulation of the present invention adds an appropriate proportion of SiC to the addition of CMA fine powder, which makes the stopper rod tip less prone to nodulation, has good anti-clogging performance, and has good oxidation resistance.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A refractory material for preventing nodule formation on plug rod heads, characterized in that: The refractory material for the stopper rod head includes powder and resin base material. By weight percentage, the powder includes 56-66% tabular corundum, 5% magnesia, 8% activated alumina, 0-8% CMA fine powder, 15% graphite, 3% Si powder, 3% Al powder, and 0-8% SiC. The resin base material is phenolic resin, which accounts for 5% of the weight of the powder.

2. The refractory material for preventing nodulation of the stopper rod head according to claim 1, characterized in that: The particle size of tabular corundum is 0-1 mm, and the Al2O3 content in tabular corundum is ≥98%.

3. The refractory material for preventing nodulation of the stopper rod head according to claim 2, characterized in that: The particle size of the tabular corundum is 325 mesh, and the Al2O3 content in the tabular corundum is ≥98%.

4. The refractory material for preventing nodulation of the stopper rod head according to claim 1, characterized in that: The particle size of the magnesia is 180 mesh, and the MgO content in the magnesia is 97% to 98%.

5. The refractory material for preventing nodulation of the stopper rod head according to claim 1, characterized in that: The particle size of the activated alumina is 325 mesh, and the Al2O3 content in the activated alumina is ≥99wt%.

6. The refractory material for preventing nodulation of the stopper rod head according to claim 1, characterized in that: The CMA fine powder has a particle size of 200 mesh, and by weight percentage, the CMA fine powder contains 70% Al2O3, 10% MgO, and 20% CaO.

7. The refractory material for preventing nodulation of the stopper rod head according to claim 6, characterized in that: CMA fine powder contains three phases: MgAl2O4, CaAl2O4, and CaAl4O7. By weight percentage, MgAl2O4 accounts for 70%, CaAl2O4 accounts for 20%, and CaAl4O7 accounts for 10%.

8. The refractory material for preventing nodulation of the stopper rod head according to claim 1, characterized in that: The graphite has a particle size of 100 mesh, with a C content of ≥99%; the Si powder has a particle size of 325 mesh, with a Si content of ≥99%; the Al powder has a particle size of 325 mesh, with an Al content of ≥99%; and the SiC has a particle size of 325 mesh, with a SiC content of ≥98.5%.

9. A method for preparing a stopper tip for preventing nodule formation, characterized in that: It is prepared using the refractory material of the stopper rod head as described in any one of claims 1 to 8.

10. A method for preparing a stopper tip for preventing nodule formation according to claim 9, characterized in that: Includes the following steps: (1) Dry mix tabular corundum, activated alumina and magnesia, then add phenolic resin and continue mixing to obtain mixture one; (2) Mix CMA fine powder, graphite, Si powder, Al powder and SiC to obtain mixture two; (3) Add mixture 2 to mixture 1 and mix well to obtain mixture 2; (4) Press the mixture into standard bar blanks using an isostatic press; (5) Sinter the standard rod blank to obtain the stopper rod head.

Citation Information

Patent Citations

  • Stopper rod for continuous casting of high-oxygen steel

    CN113526965A